DOMINAN FACTORS RELATED TO QUALITY OF LIFE OF PATIENTS WITH END STAGE RENAL FAILURE UNDERGOING HEMODIALYSIS AT TABANAN GENERAL HOSPITAL - Parut, Anselmus Aristo; Dewi, I Gusti Ayu Puja Astuti (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2018)
Background : Renal failure is a clinical condition which irreversible reduction in renal function and need hemodialysis as replacement for kidney function. Hemodialysis is a dialysis that perform outsite the body. Indonesian Association Of Nephrology (Pernerfi) stated that new hemodialysis and active hemodialysis patients in Indonesia since 2007-2018 increased, 14.644 new hemodialysis patients and 7.276 active hemodialysis patients.Method : This is a descriptive analysis study with cross-sectional design and multiple logistic regression to identify dominant factor related to quality of life hemodialysis patients. Location of this research was Tabanan General Hospital. The sampling technique was nonprability sampling with total population were 166 patients. Data collected using insomnia questionnaire, family support questionnaire, quality if life questionnaire and complication observation form. Result : The result showed that, higher OR found in intra hemodialysis variabel (OR:180,917), which mean that intra hemodialysis complication is a dominan factor related to quality of life hemodialysis patients. Patients who had complication were more likely to have low quality of life. Further study are needed to identify factors related to intra hemodialysis complications. Keywords : Dominan factors, intra hemodialysis complications, quality if life, end stage renal failure, hemodialysis.